2018
DOI: 10.1111/1468-2427.12710
|View full text |Cite
|
Sign up to set email alerts
|

Urban Political Ecology Beyond Methodological Cityism

Abstract: The concept of planetary urbanization has emerged in recent years amongst neo‐Lefebvrian urban scholars who see urbanization as a process taking place at all spatial scales. This article analyses recent critiques of the urban political ecology (UPE) literature which argue that much of the work in the field has been guilty of focusing exclusively on the traditional bounded city unit rather than urbanization as a process. In response, the article reviews various strands of the UPE literature which have (always) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 83 publications
0
39
0
Order By: Relevance
“…Scholars have also analysed imaginaries of parks, the cultural meanings of parks in a neoliberal frame and the transformation of parks into sites of capital exploitation. Other studies have broadened methodological approaches, suggesting the importance of everyday practices, experiences and contexts in understanding the transformations and interactions (Connolly 2019). Overall, research has indicated an expansion of work concerned with the negative effects of urban development which is taking place under the umbrella of greening.…”
Section: Framing Urban Parksmentioning
confidence: 99%
“…Scholars have also analysed imaginaries of parks, the cultural meanings of parks in a neoliberal frame and the transformation of parks into sites of capital exploitation. Other studies have broadened methodological approaches, suggesting the importance of everyday practices, experiences and contexts in understanding the transformations and interactions (Connolly 2019). Overall, research has indicated an expansion of work concerned with the negative effects of urban development which is taking place under the umbrella of greening.…”
Section: Framing Urban Parksmentioning
confidence: 99%
“…The international research “Global Suburbanisms: Governance, Land and Infrastructure in the 21 st Century” has produced a large body of empirical, thematic, and conceptual insights and acknowledges that suburbs are today outcomes of multi‐scale, multi‐topological process and various modalities of governance that involve worldwide interactions and aspirations in a global world (Hamel & Keil, ; Keil, ). In this respect, the field of “suburban governance” (Keil 2012; 2015; ) deals with the complexity of the worldwide suburbanization phenomenon by referring to the variety of governance modes (state‐led, capital‐led and authoritarian‐led) and stimulating at the same time new conceptual perspectives of suburban spaces beyond a “methodological cityism” (Connolly, ).…”
Section: Defining Suburbs: Manifold Concepts and Theories For A Lexiconmentioning
confidence: 99%
“…Moreover, Connolly () has argued that a landscape political ecology framework can provide powerful insights into the ways in which particular landscapes can be seen as crucial sites in generating local resistance to processes of urbanisation (see also Walker & Fortmann, , p. 469). For example, Barau () identified landscape aesthetics, contact with nature, accessibility to green and open spaces/wilderness, and threats to wildlife to be some of the most important concerns to people and places experiencing possible landscape transformation in peri‐urban settings (see also Byrne & Wolch, ) .…”
Section: Towards a Landscape Political Ecology Of Urban Heritagementioning
confidence: 99%
“…However, urban political ecology has yet to examine the topic of heritage, which I contend is an area with much potential for the field. More specifically, I draw on conceptualisations of landscape within political ecology that are useful for breaking down entrenched binaries between the cultural and natural, urban and rural (see Connolly, ; Neumann, ; Walker & Fortmann, ). Through such a holistic understanding, I hope to highlight the potential of urban heritage research in contributing to sustainable development initiatives through the integration and conservation of cultural and natural components of heritage landscapes…”
Section: Introduction: Integrating Cultural and Natural Heritage In Umentioning
confidence: 99%